Dynamics of minimal residual disease in patients with multiple myeloma on continuous lenalidomide maintenance: a single-arm, single-centre, phase 2 trial. Issue 6 (June 2021) - Diamond, Benjamin; Korde, Neha; Lesokhin, Alexander M; Smith, Eric L; Shah, Urvi; Mailankody, Sham; Hultcrantz, Malin; Hassoun, Hani; Lu, Sydney X; Tan, Carlyn; Rustad, Even H; Maura, Francesco; et al.
Summary: Background Lenalidomide maintenance improves progression-free survival for patients with multiple myeloma, although its optimal duration is unknown. Clearance of minimal residual disease (MRD) in the bone marrow results in superior outcomes, although its attainment or sustainment does not alter clinical decision-making. Studies that have evaluated MRD serially are limited in length. We therefore aimed to evaluate longitudinal changes in MRD-status (dynamics) and their association with progression-free survival in patients with multiple myeloma. Methods: In this single-centre, single-arm, phase 2 study, we enrolled patients aged 18 years and older from the Memorial Sloan Kettering Cancer Center (New York, NY, USA) who had newly diagnosed multiple myeloma following unrestricted frontline therapy and an Eastern Cooperative Oncology Group Performance Status of 2 or lower, including patients who started maintenance before study enrolment. All participants received lenalidomide maintenance at 10 mg for 21 days of 28-day cycles until progression or unacceptable toxic effects for up to 5 years on protocol. The primary endpoint was progression-free survival at 60 months per protocol and key secondary endpoints were MRD rates after completion of the 12th, 24th, and 36th cycle of maintenance and the association between progression-free survival and annual measurement of MRD status. MRD was assessed from first-pull bone marrow aspirates at baseline and annually by flow cytometry per International Myeloma Working Group criteria, (limit of detection of at least 1 × 10 −5 ) up to a maximum of 5 years. Patients who completed at least four cycles of treatment were included in the analysis of the primary endpoint, and patients who had completed at least one dose of treatment on protocol were assessable for secondary endpoints. The study was registered at ClinicalTrials.gov, NCT02538198, and is now closed to accrual. Findings: Between Sept 8, 2015, and Jan 25, 2019, 108 patients (100 evaluable for the primary endpoint) were enrolled. Median follow-up was 40·7 months (95% CI 38·7–45·0). At 60 months, progression-free survival was 64% (95% CI 52–79). Median progression-free survival was unreached (95% CI unreached–unreached). MRD dynamics were assessed using 340 MRD assessments done over 5 years for 103 evaluable patients. Patients who sustained MRD negativity for 2 years (n=34) had no recorded disease progression at median 19·8 months (95% CI 15·8–22·3) past the 2-year maintenance landmark. By contrast, patients who lost their MRD-negative responses (n=10) were more likely to progress than those with sustained MRD negativity (HR infinite; p<0·0001) and those with persistent MRD positivity (HR 5·88, 95% CI 1·18–33·33; p=0·015) at the 2-year landmark. Haematological and non-haematological serious adverse events occurred in 19 patients (18%). The most common adverse events of grade 3 or worse were decreased lymphocyte count in 48 (44%) patients and decreased neutrophil count in 47 (44%) patients. One death occurred on study due to sepsis and heart failure and was considered unrelated to the study drug. Interpretation: Serial measurements of MRD allow for dynamic assessment of risk for disease progression. Early intervention should be investigated for patients with loss of MRD negativity. Sustained MRD positivity is not categorically an unfavourable outcome and might portend prolonged stability of low-level disease. Funding: Memorial Sloan Kettering and Celgene.